Pengaruh Range of Motion (ROM) Aktif Terhadap Fleksibilitas Sendi Lutut Pada Lanjut Usia - Indrayana, Tavip; Warijan, Warijan; Siswanto, Joni (Jurnal Studi Keperawatan, 2020)
ABSTRACTBackground : Joint flexibility decreases in old age due to a degenerative process resulting in changes in joints, connective tissue and cartilage in the elderly. Decreasing flexibility is also due to reduced elasticity of muscle fibers, where connective tissue in muscle fibers increases (Mariyam, 2008).Objective : The aim of this study was to analyze the effect of active exercise (ROM) on the lower extremities on increasing the flexibility of the knee joint in the elderlyMethods : This study using a quasi-experimental approach with One group pre-test and post-test design. The sampling technique uses the Slovin method of 42 people, obtained a sample of 25 elderly. Exercise is done twice a day for 8 days. Measurements were made on day 1, day 4 and day 8 of the study using a Goniometer measuring instrument..Result : The results of measurement I average of the right knee joint 117.52o, measurement II = 122.24, measurement III = 126, 36o. From the analysis with Paired simple t-Test between the measurements I and II, it was found that the different test measurements I and II t count value was equal to -1.908 with 0.068. Because sig> 0.05, it can be concluded that Ho is accepted, meaning that the average angle of ROM before and after training is the same (not different). In the different test measurements II and III the value of t count is equal to -2.152 with sig 0.042.Conclusion : Because sig <0.05, it can be concluded that Ho is rejected, meaning that there is a difference in ROM angle after training between days 4 to 8 with the first day to day 4. Thus it can be stated that active ROM exercises affect the angle of ROM of the knee joint elderly after exercise ROM between day 4 to day 8.Â Keywords: active ROM exercise, flexibility of knee joint, elderly.